PENERAPAN PEMBELAJARAN GROUP INVESTIGATION BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR KOLOID - Wijayanti, Arinda Dian; Susatyo, Eko Budi (Jurnal Inovasi Pendidikan Kimia, 2014)
This study aims to determine whether the implementation of inquiry-based learning Group Investigation Guided influential in improving learning outcomes of chemistry in competence of Colloid Systems and how the responses of teachers and students towards applied learning. Sampling used cluster random sampling technique, obtained class XI IPA 1 as the experimental class and the XI IPA 4 as control class. Retrieval of data used techniques: tests, observations, questionnaires, and documentation. The results showed that the average grade of experimentalÂ  class was higher than the control class based on the test of the right hand, with both of the posttest score of t count Â 6.89 over t table of 2.00. The results of the analysis of the magnitude of the effect between variables obtained coefficient of determination 73.38%, mean that the inquirybased learning Group Investigation Guided Contributed to increasing students cognitive learning outcomes of 73.38%. On Affective and psychomotor assessment, the average grades of the experimental class learning better than classroom control. Analysis of the questionnaire responses of teachers and students also indicated that inquiry-based learning Group Investigation Guided obtained a good response. This study concluded that the implementation of inquiry-based learning Group Investigation Guided influenced in improving learning outcomes chemistry class XI student with competencies related colloidal systems and obtained good response from teachers and students.Keywords: Group Investigation, Learning Outcomes, Inquiry-Guided